KONSEP ARTI ISLAM DALAM AL-QUR’AN - Moh Asvin Abdurrohman; Sungkono Sungkono (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2022)
Islam is one of the largest religions spread throughout the world today. Islam is also the only religion that is approved by Allah SWT. We as Muslims should be grateful for living in Indonesia, where the majority of the population is Muslim. Islam continues to grow and can be accepted by many people thanks to the efforts made by the Prophets and also our scholars. If you pay attention, Islam is also different from other religions which take the name of the religion from the name of the founder or the name of the place where it is spread. The name of the religion of Islam is a term that shows the attitude and nature of its adherents towards Allah SWT. The name Islam was born not because of a gift from a person or group of people, but comes from the Creator directly, Allah SWT. Quoting from the mui.or.id site, the word Islam comes from the words "aslama", "yuslimu", "islaaman" which means submission, obedience, and safety. Islam means submission or total submission to the teachings of Islam given by Allah SWT. Islam came to earth to build humans in peace with an attitude of total submission to Allah SWT, so that a person who is Muslim will prioritize peace in himself and on others. Also the safety of yourself and the safety of others